European Stroke Organisation guidelines on treatment of patients with intracranial atherosclerotic disease. (September 2022) - Psychogios, Marios; Brehm, Alex; López-Cancio, Elena; Marco De Marchis, Gian; Meseguer, Elena; Katsanos, Aristeidis H; Kremer, Christine; Sporns, Peter; Zedde, Marialuisa; Kobayashi, Adam; Caroff, Jildaz; Bos, Daniel; et al.
The aim of the present European Stroke Organisation guideline is to provide clinically useful evidence-based recommendations on the management of patients with intracranial atherosclerotic disease (ICAD). The guidelines were prepared following the Standard Operational Procedure of the European Stroke Organisation guidelines and according to GRADE methodology. ICAD represents a major cause of ischemic stroke worldwide, and patients affected by this condition are exposed to a high risk for future strokes and other major cardiovascular events, despite best medical therapy available. We identified 11 relevant clinical problems affecting ICAD patients and formulated the corresponding Population Intervention Comparator Outcomes (PICO) questions. The first two questions refer to the asymptomatic stage of the disease, which is being increasingly detected thanks to the routine use of noninvasive vascular imaging. We were not able to provide evidence-based recommendations regarding the optimal detection strategy and management of asymptomatic ICAD, and further research in the field is encouraged as subclinical ICAD may represent a big opportunity to improve primary stroke prevention. The second block of PICOs (3–5) is dedicated to the management of acute large vessel occlusion (LVO) ischemic stroke caused by ICAD, a clinical presentation of this disease that is becoming increasingly relevant and problematic, since it is associated with more refractory endovascular reperfusion procedures. An operational definition of probable ICAD-related LVO is proposed in the guideline. Despite the challenging context, no dedicated randomized clinical trials (RCTs) were identified, and therefore the guideline can only provide with suggestions derived from observational studies and our expert consensus, such as the escalated use of glycoprotein IIb-IIIa inhibitors and angioplasty/stenting in cases of refractory thrombectomies due to underlying ICAD. The last block of PICOs is devoted to the secondary prevention of patients with symptomatic ICAD. Moderate-level evidence was found to recommend against the use of oral anticoagulation as preferred antithrombotic drug, in favor of antiplatelets. Low-level evidence based our recommendation in favor of double antiplatelet as the antithrombotic treatment of choice in symptomatic ICAD patients, which we suggest to maintain during 90 days as per our expert consensus. Endovascular therapy with intracranial angioplasty and or stenting is not recommended as a treatment of first choice in high-grade symptomatic ICAD (moderate-level evidence). Regarding neurosurgical interventions, the available evidence does not support their use as front line therapies in patients with high-grade ICAD. There is not enough evidence as to provide any specific recommendation regarding the use of remote ischemic conditioning in ICAD patients, and further RCTs are needed to shed light on the utility of this promising therapy. Finally, we dedicate the last PICO to the importance of aggressive vascular risk factor management in ICAD, although the evidence derived from RCTs specifically addressing this question is still scarce.